Infrared Absorption Spectra of 2-Oxo-1,3-bis-(phenylhydrazono) Derivatives and Related Bis- and Tris-phenylhydrazones - Fatiadi, Alexander J. (J Res Natl Bur Stand A Phys Chem, 1967)
The infrared absorption spectra of six 2-oxo-1,3-bis(phenylhydrazones), four tris(phenylhydrazones), and six related mono- and bis-(phenylhydrazono) derivatives are presented. For comparison, partial spectra of ten selected aromatic azo compounds are also given and discussed. The important features of the absorption bands arising from the N = N (1579 to 1558 cm(−1) and 1447 to 1408 cm(−1)), N−H (bending) (1557 to 1515 cm(−1)), and Ph−N (1163 to 1123 cm(−1)) groups are presented and discussed.